Sources of resistance to democratic decline: Indonesian civil society and its trials. Issue 1 (2nd January 2021) - Mietzner, Marcus
ABSTRACT: Amidst a global wave of democratic regression, civil society has often been the last line of defence against campaigns to undermine liberal rights and freedoms. In many cases, society activists have been able to mitigate, or even arrest, anti-democratic initiatives launched by political elites with a host of vested interests. But some countries have recently seen a weakening of this democracy defence potential embedded in civil society. Using Indonesia – the world's third largest democracy – as a case study, this article shows how escalating polarization can split civil society along primordial and ideological lines, eroding its ability to offer a united pro-democracy front. In the Indonesian case, the executive also used this polarization to justify increasingly illiberal measures. In combination, polarization and increased executive illiberalism have reduced Indonesian civil society's activist resources, accelerating the country's democratic backsliding in the process.